2020
DOI: 10.1152/japplphysiol.00744.2019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heated water-based versus land-based exercise training on vascular function in individuals with peripheral artery disease

Abstract: Peripheral artery disease (PAD) is an atherosclerotic disease that is associated with poor vascular function, walking impairment, and reduced quality of life. Land-based exercise therapy (LBET) is frequently recommended to improve walking and reduce symptoms. Recently, evidence has suggested that heated-water exercise therapy (HWET) is an effective intervention for PAD. However, the efficacy of LBET versus HWET in PAD patients had not been elucidated. Therefore, we sought to compare effects of LBET with HWET o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 85 publications
1
24
0
Order By: Relevance
“…Several benefits for acute and chronic hemodynamics have been reported for heated-water immersion in PAD [12,13]. In addition, we have previously shown that exercise training in heated water promotes hemodynamic benefits, favorable vascular structural changes, and improved quality of life in PAD [14,15]. In fact, exercise in heated water demonstrated relatively higher adherence to the clinically recommended land-based training [15].…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Several benefits for acute and chronic hemodynamics have been reported for heated-water immersion in PAD [12,13]. In addition, we have previously shown that exercise training in heated water promotes hemodynamic benefits, favorable vascular structural changes, and improved quality of life in PAD [14,15]. In fact, exercise in heated water demonstrated relatively higher adherence to the clinically recommended land-based training [15].…”
Section: Introductionmentioning
confidence: 82%
“…The combined effects of exercise and full-body heating have also been recently investigated. Park et al (2020) examined the effects of a heated-water exercise (HW) protocol and a dry-land exercise (LB) protocol (treadmill training) in patients with PAD [15]. Subjects allocated to both groups participated in their mode of exercise for 12 weeks [15].…”
Section: Clinical Applications Of Heat Therapymentioning
confidence: 99%
See 3 more Smart Citations